Estrogen receptor 1 appears essential for fetal viability in a murine model of premature birth. (15th December 2022) - Schmiedecke, Stacey S.; Thagard, Andrew S.; Edwards, Sarah M.; Talley, Rebecca L.; Dornisch, Elisabeth M.; Damicis, Jennifer R.; McLane, Michael; Burd, Irina; Napolitano, Peter G.; Ieronimakis, Nicholas
Abstract: Problem: Protective effects for adult neurological disorders have been attributed to sex hormones. Using a murine model of prematurity, we evaluated the role of estrogen signaling in the process of perinatal brain injury following exposure to intrauterine inflammation. Method of study: Intrauterine lipopolysaccharide (LPS) was used to invoke preterm labor and fetal neuroinflammation. Fetal brains were analyzed for changes in Esr1, Esr2 and Cyp19 . Dams heterozygous for the Esr1 knockout allele were also given intrauterine LPS to compare delivery and offspring viability to wild type controls. Results: The upregulation in inflammatory cytokines was accompanied by an increase in Esr1 and Esr2 transcripts, though protein levels declined. Cyp19 did not differ by mRNA or protein abundance. Offspring from Esr1 mutants were larger, had a longer gestation and significantly greater mortality. Conclusions: Estrogen signaling is altered in the fetal brains of preterm offspring exposed to neuroinflammatory injury. The reduction of Esr1 and Esr2 proteins with LPS suggests that these proteins are degraded. It is possible that transcriptional upregulation of Esr1 and Esr2 occurs to compensate for the loss of these proteins. Alternatively, the translation of Esr1 and Esr2 mRNAs may be disrupted with LPS while a feedback mechanism upregulates transcription. Intact Esr1 signaling is also associated with early preterm delivery following exposure to intrauterine LPS. A loss of one Esr1 allele delays this process, but appears to do so at the cost of fetal viability. These results suggest estrogen signaling plays opposing roles between maternal and fetal responses to preterm birth.